The Influence of Transformational Leadership on Organization Innovation in Malaysian Manufacturing Industry - Chan, Shiau Wei; Ang, Sye Fang; Andleeb, Naima; Ahmad, M.F.; Zaman, Izzuddin (ExcelingTech, 2019)
In today industry, transformational leadership has become the top influential factor that affects the organization innovation. The aim of this study is to determine the level of transformational leadership (idealized influence, inspirational motivation, intellectual, and individual consideration) for employees in the Malaysian manufacturing industry. This study also identifies the influence of transformational leadership on organization innovation in the Malaysian manufacturing industry. This research involved the leaders of admin level in manufacturing industry Batu Pahat, Johor, Malaysia. The survey questionnaire was distributed to 165 respondents. The result indicated that Intellectual Stimulation was the highest level for employees in the manufacturing industry. However, Individual Consideration was the most significant correlation to organization innovation in the manufacturing industry. This quantitative research is important to provide better information relating to the relationship between transformational leadership and the organization innovation so that the admin level leader can obtain a clear understanding of how to guide their followers effectively in an organization.